Peran Teman Sebaya dalam Menyelesaikan Tugas Kuliah Mahasiswa Semester 3 PAI UIN Gusdur - Dwi Siska; Ma’mun Hanif (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
With an emphasis on third-semester students, this study investigates the function of peer support in assisting students at UIN K.H. Abdurrahman Wahid Pekalongan in completing academic assignments. The purpose of the study is to investigate how peer relationships affect academic achievement, especially in cooperative learning settings. Purposive sampling was utilized to select 20 students for in-depth interviews in order to gather data. According to a thematic analysis of the interviews, students' academic performance is positively impacted by peer support, which includes practical, emotional, and informational assistance. Over-reliance on peers, however, may impede the growth of autonomous academic abilities. According to the results, creating a peer-supportive atmosphere can increase motivation and output while striking a balance with independence. This study advances our knowledge of how peers engage in classrooms and offers useful advice for enhancing cooperative learning.